ANALISIS VEGETASI PERINTIS LOKAL DI LAHAN BEKAS TAMBANG PASIR KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Raizal Fahmi Solihat (Jurnal Belantara, 2022)
Mining activities generally use large tracts of land, utilize non-renewable resources, produce a lot of waste, and make land degraded and unproductive. This happened on one of the former sand mining areas in Cimalaka sub-district, Sumedang Regency. Rehabilitation techniques by planting pioneering plants known as swapping are effective techniques. Pioneer plants are plants that start the formation of a habitat. This study aims to obtain information about the structure and composition of pioneering plants in the former sand mining quarry in the Cimalaka sub-district of Sumedang Regency. This research is descriptive, using a survey method with exploration, the research sample is a local pioneering plant that is included in the sampling plot found at the research location. The results showed that the structure at the level of pioneering vegetation in the former sand fields of Cimalaka subdistrict, namely shrubs Eleusine indica L. and Axonopus compressus, seedling plant Calliandra calothyrsus, Gliricidia sepium, Ageratum conyzoides L. Imperata cylindrica L. Saccharum spontaneum L. Vetiveria zizanioides Stapf. dan Coleus soutellarioides L.